Beyond Policy: Strengthening District Level Access to Surgery Is Critical to Achieving Surgical Equity in Universal Health Coverage; Comment on "Improving Access to Surgery Through Surgical Team Mentoring - Policy Lessons From Group Model Building With Local Stakeholders in Malawi" - Jaymie A. Henry (Kerman University of Medical Sciences, 2023)
District level access to surgical care has been identified as the rate limiting step to increasing access to the bottom billion and relies on a complex interplay of patient-related and system-based factors that underlie the provision of quality surgical care at point of care. Surgical mentoring via visiting teams, use of current proprietary technologies to enhance communication, establishment of a national surgical coordinator and multi-stakeholder engagement with creative cost-sharing have all demonstrated promising results. Regardless of strategic implementation frameworks, system-based thinking coupled with implementation science with practical solutions will be necessary to inform stakeholders on the best way forward in their respective geographic field of work charting a path towards surgical equity in universal health coverage (UHC).